A Collision Model for Protective Structure with Gradient Metallic Cellular Material under Low Velocity Impact - Dengbao Xiao; Guiping Zhao (Shock and Vibration)
During quasi-static compressive process, the gradient metallic cellular material can be divided into deformed region and undeformed region before the material is compressed compactly. The deformation mode of the gradient metallic cellular material is not the same as that of homogeneous metallic cellular material. Meanwhile, no plateau stress is observed in the crushing stress versus strain curve of the gradient metallic cellular material. A formula of calculating crushing stress of the gradient metallic cellular material is presented. Subsequently, a collision model for protective structures with gradient metallic cellular material is presented to investigate the vibration isolation of the large mass protection under low velocity impact based on Lagrange’s equation of the second kind. The effects of the gradient metallic cellular material on the acceleration peak of inner protected structure are theoretically discussed. And the results show that adopting gradient metallic cellular material instead of homogeneous metallic cellular material with equivalent mass can decrease the peak acceleration value of the inner protected structure.